Challenges and Opportunities in Health Care Management - Gurtner, Sebastian; Soyez, Katja (Springer International Publishing : Imprint: Springer, 2015)
This contributed volume draws a vital picture of the health care sector, which, like no other is affected by technology push and stakeholder pull. Innovative product and service solutions emerge, which have to integrate different stakeholders' interests. This book studies current challenges in health care management from different perspectives. Research articles analyze the situation in the health care sector and present solutions in the following areas: the health care system; hospitals; teams in health care; patients' perspectives; assessment of technologies and innovations; and toolkits for organizing health care. All these contributions summarize pressing hot topics in the health care sector, analyze their future potential, and derive managerial implications. Outstanding best practices throughout Europe are presented in the case study section of the book. Consequently, the book closes the gap between science and practical application by addressing not only readers from academia but also practitioners working in the health care industry.